COMPARISON OF SOLIFENACIN AND MIRABEGRON FOR THE TREATMENT OF OVERACTIVE BLADDER - Nasir Jamil, Muhammad; Sadia Irum; Ehsan ul Islam (Journal of Ayub Medical College Abbottabad, 2023)
Background: Overactive bladder is mostly treated with a combination of behavioural interventions and commonly prescribed anti-muscarinic medication therapy, including solifenacin, which has considerable side effects and lowers the quality of life. Mirabegron relaxes the detrusor muscle and is a recently approved drug for the treatment of OAB. This study examined the effectiveness and safety of two medications, solifenacin and mirabegron. Methods: This study was a comparative cross-sectional study conducted at Sami Medical Center, Abbottabad for a period of 6 months from August 2022 to January 2023. Female patients of aged ‰¥18 years with symptoms of OAB were enrolled. Results: Current study showed that the average age of patients was 37.47±12.48 years in Group S and 39.93±7.93 in Group M. The population consists of 60 (100%) females. After 4 weeks of follow up dizziness, dry mouth, constipation hypertension and blurred vision were found insignificant between both groups with p-values of 0.312, 0.161, 0.076, 0.076, and 0.313 respectively. OABSS score improved significantly and after therapy 4.20±1.32 in Group S and 3.43±1.13 in Group M. There was no significant difference in frequency of treatment withdrawal p-value 0.150. Conclusion: When it comes to relieving symptoms of OAB, both solifenacin and mirabegron are effective. The OABSS improved with both drugs; however, mirabegron was associated with fewer treatment-related adverse events. We advocate using mirabegron as the first-line treatment. Solifenacin can be utilized if patients are no longer getting the desired effects from Mirabegron.